'I have a different kind of brain'—a script-centric approach to interactive narratives in games. Issue 1 (2nd January 2019) - Engström, Henrik
ABSTRACT: In a computer game narrative, a user influences the ordering of events. To model this behaviour, game designers and writers need to use some kind of programming primitives. A computer game script will hence differ from, for instance, a movie screenplay in that traditional dialogue text is complemented with some textual or visual logic formalism. Not all groups involved in production of a game have a programming background and may therefore be unable to easily comprehend such formalisms. This paper presents a novel approach to game dialogue writing where traces from play-throughs are used as the core of the script. Alternative branches are identified and presented in relation to the main trace. The approach has been implemented in a tool that has been used successfully by three professional writers in mobile game production. The results indicate that this is a promising approach to enable non-programmers to work with interactive narratives.